Dampak Kepribadian Mahasiswa KPI-D dalam Berinteraksi Sosial di Lingkungan Fakultas Dakwah - Ainul Mardiyah; Siti Nurwahidah Lubis; Shandy Viona Br Sebayang; Rizky Andriansyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the impact of personality types—introvert, extrovert, and ambivert—on the social interaction abilities of KPI-D students within the Faculty of Da'wah and Communication. Social interaction is a crucial aspect of campus life, yet personality differences often create challenges in communication and social adaptation. Using interview methods with six respondents representing different personality types, the research found that introverted students tend to face difficulties in engaging in social activities, while extroverted students easily socialize but may lose academic focus. Ambivert students demonstrate flexibility, yet sometimes struggle with indecision in social situations. The study highlights the importance of developing social skills tailored to each personality type and fostering an inclusive, tolerant campus environment. These findings are expected to contribute to strategies for improving communication and social development among students.